Investigation of the Acid Strength Effects on Bipolar Membrane Electrodialysis - Erkmen, Jülide; Yapici, Sinan (Journal of Membrane and Separation Technology, 2014)
The purpose of this paper is to investigate acid strength effects on the same system for production of two different acids. Production of two different acids from their salts was carried out by electro dialysis (ED) using bipolar membranes (BPM). An virulent acid hydrofluoric acid and an weak acid boric acid were produced, all data were recorded and compared. Result of the study, in electro dialysis of acids and base, acid strength play an important role in terms of the efficiency of the process. Current efficiency was calculated very high at all processes for this electro dialysis (EDBM) system. This results in a growing demand for alternative process solutions such as Electro dialysis with Bipolar Membranes (EDBM).